Celestinas y majas en la obra de Goya, Alenza y Lucas Velázquez - Rachel Schmidt (Celestinesca, 2021)
This article examines the development of two iconographic streams of Celestina and maja imagery in nineteenth-century art, both established by Goya: the satirical, which is often expressed through the medium of print and highlights prostitution as commercial trafficking, and links it to other social phenomena such as forced marriage and vagrancy; and the sentimental or picturesque, which is often expressed through paint media and presents an idealized or sensual view of the maja. Leonardo Alenza y Nieto (1807-1845) develops Goya's critical viewpoint on prostitution by incorporating marginal male figures into the imagery, thus bringing into the frame relations between female prostitutes, clients, beggars and even male prostitutes. Eugenio Lucas Velázquez (1817-1870), painting during the period of legalized prostitution in which the sex trade was moved into medically and state controlled brothels, works out of the sentimentalized tradition, depicting the majas as victims of now bestialized celestinas or as merely attractive folkloric figures.